An ecological response index for simultaneous prediction of eutrophication and metal pollution in large rivers. (15th September 2019) - Jaiswal, Deepa; Pandey, Jitendra
Abstract: The ecological responses of riverine ecosystems are strongly influenced by anthropogenic perturbations. However, high-resolution quantitative shifts in the 'ecosystem responses' to multiple human pressures in riverine ecosystems are not well understood. Given that, in most of the anthropogenically impacted rivers, eutrophy and metal pollution occur simultaneously, we explored FDAase activity, microbial quotient, and a sum of six heavy metals in an empirical relationship to develop an 'ecological response index' (ERI). The FDAase, a measure of fluorescein diacetate hydrolytic activity, and microbial quotient, the proportion of microbial biomass-C to the total organic carbon (Cmic /TOC) were used to address 'ecosystem responses' to C-eutrophy and metal pollution. We analyzed 1404 water samples and 2808 sediment samples collected from the land-water interface (LWI) and riverbed sediment (50 m reach) of 24 sites along a 528 km main stem and from 30 sites downstream two point sources of the Ganga River. The index was compare to Carlson's trophic state index (TSI) to quantify eutrophy and Håkanson's risk index (RI) and modified ecological risk index (MRI) for metal pollution. The ERI showed strong correlation with TSI (R 2 = 0.70–0.97; p < 0.001), RI (R 2 = 0.76–0.94; p < 0.001) and MRI (R 2 = 0.76–0.96; p < 0.001). The ERI developed here is the first 'response index' against multiple human pressures, able to quantitatively predict C-eutrophication and metal pollution simultaneously in large rivers. Graphical abstract: Image 1 Highlights: We developed an ecological response index (ERI) to simultaneously predict C-eutrophy and metal pollution. The FDAase and microbial quotient were used to address 'ecosystem response'. A scale of 0–320 has been used to predict different levels of C-eutrophy and metal pollution. The index developed compare well to Carlson's trophic state index, Håkanson's risk index and modified ecological risk index. The ERI developed here is the first 'response index' against multiple human pressures.